Methylation site within a facultatively persistent sequence in the macronucleus of Tetrahymena thermophila. - White, T C (1986)
DNA methylation occurs at the adenines in the somatic macronucleus of Tetrahymena thermophila. We report on a methylation site within a DNA segment showing facultative persistence in the macronucleus. When the site is present, methylation occurs on both strands, although only 50% of the DNA molecules are methylated.